Prevalence of Advanced Diabetic Eye Disease among diabetic patients in a tertiary care hospital in South India - Ksheeraja Y; Ramya M (International Journal of Retina, 2022)
Introduction:To analyze the Prevalence of advanced diabetic eye disease(ADED) among diabetic patients Methods:This was a prospective cross-sectional study in a tertiary care hospital. A total of 1650 patients with a history of type 2 diabetes who visited ophthalmology department were enrolled in study. History regarding socioeconomic status, literacy level, duration of diabetes, comorbidities, medications, HbA1c levels were analyzed. Visual acuity,Slit-lamp, fundus examination were done.Medical/surgical intervention was done to restore vision. Results: A total of 1650 patients with a history of type 2 diabetes were analyzed. Among them 327 patients had fundus changes of diabetic retinopathy, hence the prevalence of DR among diabetics was 19.81%. Out of 327 patients, 53 patients had advanced diabetic eye disease and the prevalence of ADED among Diabetics was 3.20%. The mean age of the patients was 50.91+/- 9.06years.There were 42 (79.24%)males and 11 (20.7%)females.24 (45.28%)patients had vision of 6/6 - 6/60, 28 (52.83%|) patients had vision 5/60-CFCF.15(28.30%) patients had PDR with vitreous hemorrhage.12 patients (22.64%) had PDR with subhyaloid hemorrhage,11 patients (20.75%) had PDR with FVP sparing macula,13 patients(24.52%) had PDR with FVP involving the macula,2 patients(3.77 %) had PDR with Neovascular glaucoma.34 patients (64.15%) underwent PRP,19 patients (35.84 %) needed surgical intervention. Conclusion: This study shows that the prevalence of diabetic retinopathy among diabetic patients was 19.81%. The prevalence of Advanced Diabetic Eye Disease among diabetic patients was 3.2%. Hence Effective implementation of primary, secondary and tertiary prevention strategies has the potential to significantly reduce blindness due to DR.